Dostarlimab for Primary Advanced or Recurrent Endometrial Cancer - Mirza, Mansoor R; Chase, Dana M; Slomovitz, Brian M; dePont Christensen, René; Novák, Zoltán; Black, Destin; Gilbert, Lucy; Sharma, Sudarshan; Valabrega, Giorgio; Landrum, Lisa M; Hanker, Lars C; Stuckey, Ashley; et al. (The New England journal of medicine, 2023)
BACKGROUND: Dostarlimab is an immune-checkpoint inhibitor that targets the programmed cell death 1 receptor. The combination of chemotherapy and immunotherapy may have synergistic effects in the treatment of endometrial cancer. METHODS: We conducted a phase 3, global, double-blind, randomized, placebo-controlled trial. Eligible patients with primary advanced stage III or IV or first recurrent endometrial cancer were randomly assigned in a 1:1 ratio to receive either dostarlimab (500 mg) or placebo, plus carboplatin (area under the concentration-time curve, 5 mg per milliliter per minute) and paclitaxel (175 mg per square meter of body-surface area), every 3 weeks (six cycles), followed by dostarlimab (1000 mg) or placebo every 6 weeks for up to 3 years. The primary end points were progression-free survival as assessed by the investigator according to Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1, and overall survival. Safety was also assessed. RESULTS: Of the 494 patients who underwent randomization, 118 (23.9%) had mismatch repair-deficient (dMMR), microsatellite instability-high (MSI-H) tumors. In the dMMR-MSI-H population, estimated progression-free survival at 24 months was 61.4% (95% confidence interval [CI], 46.3 to 73.4) in the dostarlimab group and 15.7% (95% CI, 7.2 to 27.0) in the placebo group (hazard ratio for progression or death, 0.28; 95% CI, 0.16 to 0.50; P<0.001). In the overall population, progression-free survival at 24 months was 36.1% (95% CI, 29.3 to 42.9) in the dostarlimab group and 18.1% (95% CI, 13.0 to 23.9) in the placebo group (hazard ratio, 0.64; 95% CI, 0.51 to 0.80; P<0.001). Overall survival at 24 months was 71.3% (95% CI, 64.5 to 77.1) with dostarlimab and 56.0% (95% CI, 48.9 to 62.5) with placebo (hazard ratio for death, 0.64; 95% CI, 0.46 to 0.87). The most common adverse events that occurred or worsened during treatment were nausea (53.9% of the patients in the dostarlimab group and 45.9% of those in the placebo group), alopecia (53.5% and 50.0%), and fatigue (51.9% and 54.5%). Severe and serious adverse events were more frequent in the dostarlimab group than in the placebo group. CONCLUSIONS: Dostarlimab plus carboplatin-paclitaxel significantly increased progression-free survival among patients with primary advanced or recurrent endometrial cancer, with a substantial benefit in the dMMR-MSI-H population. (Funded by GSK; RUBY ClinicalTrials.gov number, NCT03981796.).
Keywords: Humans; mikrosatelitní nestabilita; Double-Blind Method; Microsatellite Instability; Female; Carboplatin; protokoly protinádorové kombinované chemoterapie; Endometrial Neoplasms; inhibitory kontrolních bodů; lidé; humanizované monoklonální protilátky; dvojitá slepá metoda; Antibodies, Monoclonal, Humanized; ženské pohlaví; DNA Mismatch Repair; Immune Checkpoint Inhibitors; paclitaxel; Antineoplastic Combined Chemotherapy Protocols; oprava chybného párování bází DNA; nádory endometria; lokální recidiva nádoru; Paclitaxel; karboplatina; Neoplasm Recurrence, Local